A new species of Huarpea Pate, 1947 from Colombia and redescription of H. wagneriella (du Buysson, 1904) (Hymenoptera: Sapygidae) - Fernández, Fernando; Sarmiento, Carlos E. (Zootaxa, 2015)
Huarpea colombiana sp. nov. from Colombia (Meta) is described and illustrated. This is the first record of the family Sapygidae for Colombia and northern South America. Huarpea wagneriella (du Buysson, 1904) is redescribed. An updated key to Neotropical genera and species of Sapygidae is given.